Studies On The Comparative Feed Efficacy Of Bombyx Mori (L.) (Lepidoptera: Bombycidae) Fed With Silver Nanoparticles (Agnps) And Spirulina Treated Mr2 Mulberry Leaves In Relation To Growth And Development - GANESH PRABU P.; SENTHAMARAI SELVI . E; SELVISABHANAYAKAM; MATHIVANAN V; PRADHAP M; VIVEKANANTHAN T (International Journal of Pharma and Bio Sciences, 2011)
Silkworm Bombyx mori is an important economic insect and also a tool to convert leaf protein into silk. The industrial and commercial use of silk, the historical and economic importance of production and its application in all over the world finely contributed to the silkworm promotion as a powerful laboratory model for the basic research in biology. The mulberry leaf is the only important source of the silkworms. The present study has been undertaken to the effectiveness of foliar applications of silver nanoparticles (AgNps) (25%) and single cell protein (SCP) containing microalgae Spirulina (0.03%) treated MR2 mulberry leaves fed with the popular Indian bivoltine hybrid (CSR2×CSR4) silkworm B. mori larvae (3rd, 4th and 5th instar) to study the larval growth and development (length, width and weight) and economic parameters like cocoon (length, width and weight) shell and pupal weight were significantly increased than control group. This study was indicated that the AgNps and Spirulina exhibit the presence of certain growth stimulant and can be used to increase the silk yield in commercial silkworm rearing.